THE IMPACT OF CUSTOMER ENGAGEMENT ON PURCHASE INTENTION: CUSTOMER VALUE CREATION AS AN INTERMEDIARY - Conny Tjandra Rahardja; Alfian Dwijati Kuncara (LPPM STIE YKPN Yogyakarta, 2023)
The aim of this research is to examine the influence of customer engagement on businesses' social media accounts on purchase intention, with social value, hedonic value, and co-creation value as mediating variables. The sampling technique employed purposive sampling, with a total of 520 respondents. The analysis was conducted using the Smart PLS 3.0 statistical tool. The results of this study indicate a significant direct impact of customer engagement on businesses' social media accounts on social value and purchase intention, which is considerably higher compared to other variables in this research. The indirect influence of consumer engagement on purchase intention is partially mediated by customer value creation. Among the sub-variables of customer value creation used in the study, social value was found to mediate marginally. In addition to conducting mediation tests, the researcher also performed a path analysis. The discussion, implications, and research recommendations are presented in this article.